'Street citizenship': informal processes of engaging youth as citizens through research and knowledge exchange in three African cities. Issue 3 (1st September 2020) - van Blerk, Lorraine; Shand, Wayne; Hunter, Janine
ABSTRACT: Street-living youth are deprived of formal citizenship due to their age and exclusion from school or other state apparatus through which cultural/moral values are shared. Drawing on participatory longitudinal data from research in three African cities, this paper explores a nuanced 'street citizenship' as facilitated through informal processes and spaces, suggesting 'street citizenship' can be active and sometimes activist, with the potential to challenge understandings of poverty and marginalization in childhood more widely. Street-living youth's lived citizenship practices are developed at various scales within communities, cities and states and through engagement with local communities, civil society, policymakers and governments.